MASTERING ENGLISH: USM ASSISTS THROUGH LITERATURE COMPONENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 26 May 2015 – In ensuring the mastery of the English language among students especially those in schools, Universiti Sains Malaysia (USM) through the School of Educational Studies (PPIP) undergraduates majoring in “Teaching of English to Speakers of Other Languages” (TESOL) teamed up with Sekolah Menengah Kebangsaan (SMK) Penang Free and SMK Convent Greenlane in organising a play based on the English Language Literature component (KOMSAS) entitled “Penang English Literature Drama Showcase”, staged at the Panggung Pelenggam Cahaya, here today.